2015
DOI: 10.2340/16501977-1994
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometric assessment of different dimensions of natural walking during the first year after stroke: Recovery of amount, distribution, quality and speed of walking

Abstract: Objectives:To describe the course of walking behaviour over a period of 1 year after stroke, using accelerometry, and to compare 1-year data with those from a healthy group. Design: One-year follow-up cohort study. Subjects: Twenty-three stroke patients and 20 age-matched healthy subjects. Methods: Accelerometer assessments were made in the participants' daily environment for 8 h/day during the 1 st (T1), 12 th (T2) and 48 th (T3) weeks after stroke, and at one timepoint in healthy subjects. Primary outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…Overall, persons with a-SAH spent 25% less time in PA than healthy controls (105 vs 140 min/24 h, respectively). However, the total volume of walking activities did not differ between groups; this is in line with an accelerometer-based study on walking activities in patients with stroke [ 40 ]. Furthermore, compared with controls, persons with a-SAH participated particularly less in cycling activities and, to a lesser extent, in running activities.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, persons with a-SAH spent 25% less time in PA than healthy controls (105 vs 140 min/24 h, respectively). However, the total volume of walking activities did not differ between groups; this is in line with an accelerometer-based study on walking activities in patients with stroke [ 40 ]. Furthermore, compared with controls, persons with a-SAH participated particularly less in cycling activities and, to a lesser extent, in running activities.…”
Section: Discussionsupporting
confidence: 86%
“…The autocorrelation coefficient refers to the correlation of a time series with its own past or future values. The closeness of the autocorrelation coefficient to 1.0 reflects high step or stride regularity [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Differences between healthy adults and people with neurologic pathologies were found in other studies using IMUs and some of the variables that we collected to form the ImDGI score (Table S2). Sanchez et al and Iosa et al showed mobility impairments in terms of decreased stride regularity and symmetry, and lower harmonic ratio values (a measure of gait smoothness) in participants with CVA when compared to healthy participants …”
Section: Discussionmentioning
confidence: 97%